O Geogebra no ensino de Física: propostas de aplicação para o ensino do movimento Harmônico simples - Carmo, Rodrigo (2017)
In this work we discuss two important movements that are part of the curriculum of the physical discipline of physics in high school, wich are classified as part of a set of phenomena that constitute as an Simple Harmonic Motion (SHM). Namely, the pendulum movement and the projection of uniform circular motion on one of the cartesian axes. In both situations we have a SHM. We have developed dynamic simulations of these phenomena using GeoGebra software. This approach allows user’s, teacher and student, the establish a visual connection between geometry, algebra and the physical concepts present in the studied subjects, it allows interactions that go beyond the conventional simulators, such as having full access to the programming used, allowing user’s to control it at will. We also elaborated two routes of usage, one for each simulator. We applied the simulators in the environment a suggestion of didactic application of our simulators.